THE INFLUENCE OF WORK DISCIPLINE AND WORKLOAD ON EMPLOYEE PERFORMANCE (Study on Community Empowerment for Helath Service Employees At California District) - John Zysman; Arnaud Costinot (PT. Radja Intercontinental Publishing, 2022)
This study aims to determine